Investigating English textbooks used in Taiwanese senior high schools from an ELF perspective - Luo, Wen-Hsing (Studies in English Language and Education, 2024)
English textbooks are the major learning resources for Taiwanese students to gain access to the target language. This study examines the English textbooks used in senior high schools (Grade 10 to Grade 12) in Taiwan from the perspective of English as a lingua franca (ELF). To prepare students to use English for international communication, it is worthwhile to examine how English textbooks incorporate an ELF orientation. Through textbook analysis, I investigated the following questions: (1) how the English textbooks used in senior high schools in Taiwan integrate an ELF perspective, and (2) how ELF attributes are manifested in the textbooks through various subject matter, exercises, and activities. The study finds that the examined textbooks partially incorporated an ELF orientation, and the ELF attributes were manifested to different extents. The main ELF attributes in the textbooks were helping learners understand the use of ELF and encouraging English use in relation to learners experiences and localities. Additionally, the study reveals that the ELF attributes were displayed in various types of activities and exercises, while the subject matter of the textbook units covered a wide range of topics. In light of the findings, I make suggestions for the development of ELF-oriented textbooks at the senior high school level, such as helping English learners to understand the use of ELF by introducing English varieties, encouraging the use of intercultural communication strategies, taking into account of learners experience in learning English, and promoting learners awareness of ELF.